Unveiling the dynamics of social credit determinants using fuzzy cognitive mapping and system dynamics - Pereira, L.; Correia, R.; Ferreira, F.; Falcão, P.; Costa, R. (International Transactions of Operations Research, 2023)
Fighting poverty and social inequality are baseline principles of social credit. This type of microcredit has thus increasingly attracted academics and practitioners’ attention, particularly after Muhammad Yunus was awarded the 2006 Nobel Peace Prize. Researchers acknowledge that social credit is extremely important and that it should be taken seriously. However, studies examining the dynamics of its determinants are still extremely rare. This gap needs to be filled because the objectives of social credit are quite different from those of other types of credit, going beyond profit and embracing social concerns. Adopting a constructivist, processoriented stance that combined fuzzy cognitive mapping and the system dynamics (SD) approach, the present research sought to develop and analyze a cognitive structure that elucidates the dynamics of social credit determinants over time. Face-to-face group work sessions were held with a panel of professional credit analysts, and the results reveal that the combined use of fuzzy cognitive mapping and SD provides a clearer understanding of the dynamics of these determinants over time. The advantages, limitations, and implications of the proposed methodology are discussed.